-16+4n=(1+2n)

Simple and best practice solution for -16+4n=(1+2n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16+4n=(1+2n) equation:


Simplifying
-16 + 4n = (1 + 2n)

Remove parenthesis around (1 + 2n)
-16 + 4n = 1 + 2n

Solving
-16 + 4n = 1 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
-16 + 4n + -2n = 1 + 2n + -2n

Combine like terms: 4n + -2n = 2n
-16 + 2n = 1 + 2n + -2n

Combine like terms: 2n + -2n = 0
-16 + 2n = 1 + 0
-16 + 2n = 1

Add '16' to each side of the equation.
-16 + 16 + 2n = 1 + 16

Combine like terms: -16 + 16 = 0
0 + 2n = 1 + 16
2n = 1 + 16

Combine like terms: 1 + 16 = 17
2n = 17

Divide each side by '2'.
n = 8.5

Simplifying
n = 8.5

See similar equations:

| -30x^4+20x^2-24x+6x^3+4= | | 7f+18=4f+-33 | | 5x-23=3x+25 | | y=800+0.25x | | 2(4)-5(2x-10)=18 | | 4S+11=15 | | b=-12+9c+2x | | 3-3x=5-4x | | (x+9)4=3 | | 7(6-x)=5x-2(5x-6) | | (v+5)(v-2)=0 | | 8(4)=w(7)-w(3) | | 5r+-9=-7r+6 | | -1(3x+1)=-7 | | 4(2x+b)-3(4-3c)=5b+6x | | (2x-3)/(-1)=(1-4x)/2 | | 27y-18= | | 5r^2-22r+21=0 | | 2x-1/21=x-5/24 | | 5n+5=2p | | 50=3x+5x | | 180=2(4y-15)+7 | | 7(t-8)+50=10t+14+2t | | 8n-6+1n+10= | | .1(40x)-1/2(16) | | 3(x-7)+2x=10 | | 3(x+2)=0.55(2x+3) | | 180x(2x+8)= | | X+.05=2.10 | | (-3g)-(-1)= | | 4u+9=69 | | 5q+14=72q |

Equations solver categories